2020
DOI: 10.37605/pjhssr.3.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Islam and Women’s Rights of Education: Mandatory or Forbidden

Abstract: Women have been subjected to marginalization and various kinds of discrimination since ancient times, including the right of education. It was only in the late 20th century that women were allowed formal education. However, in today’s world, many rights given to women by Islam are still denied, including education. The famous hadith “acquisition of knowledge is binding on all Muslims” makes it clear that education in Islam is equally important, irrespective of the sex. However, in many other religions and cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…Even research (Aune, 2014;Darwin, 2018) demonstrates that religion and gender are linked. In light of this, (Khan et al, 2020) conclude that Islam does not restrict women's access to education. Naturally, research (McClendon et al, 2018) provides an understanding of the role of religion that enables the creation of an ideal educational environment for women.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Even research (Aune, 2014;Darwin, 2018) demonstrates that religion and gender are linked. In light of this, (Khan et al, 2020) conclude that Islam does not restrict women's access to education. Naturally, research (McClendon et al, 2018) provides an understanding of the role of religion that enables the creation of an ideal educational environment for women.…”
Section: Literature Reviewmentioning
confidence: 96%
“…According to Dollar-Gatti (1999) in his study highlights significantly on the issue of macro-economic effects of women's education. The study finds out that, there is a strong correlation between secondary school enrollment of women and per capita income and found that gender inequality in education negatively affects economic growth but women who receive a low level of education, cultural elements, and civil rights are also affected by gender inequality Many previous studies highlighted the various factors explaining economic growth (Raza et al, 2020;Khan et al, 2019;Khan et al, 2020;Jehan et al, 2921;Khan et al, 2021;Khan et al, 2018;Uddin et al, 2023). In the light of Fennell ( 2009) in his literature review that gender inequality has reduced the economic growth of a country for minimizing the poverty and increasing development.…”
Section: Literature Reviewmentioning
confidence: 99%